Analysis of Indonesian Students' Intercultural Communication Competence (ICC) During Internships in Japan - Cecep Wahyu Hoerudin; Baby Poernomo; Supriyono Supriyono; Md. Ahsan Habib (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Internships abroad are a strategic opportunity for Indonesian students to hone professional skills, expand networks, and enhance competitiveness in the global job market. One country that many Indonesian students are interested in for internships is Japan. However, many students encounter challenges in cross-cultural communication. This is a qualitative study with a case study approach. Data collection was conducted through semi-structured interviews with Indonesian students who were interning in Japan. To maintain data validity, the researcher used source triangulation. The study results show that Indonesian students interning in Japan in the early period of their stay and internship still experience difficulties adapting to the work environment in Japan, which has high-quality standards, such as levels of discipline, kaizen, seishen, meishi kokan, and doryoku. However, with determination and strong desire, they managed to adapt to the new environment with appropriateness, effectiveness, and adaptability achievements in accordance with the company's expectations in Japan